The effect of fiscal system reform on fiscal policy outcomes. (4th October 2019) - Lee, Sangmok; Esfahani, Hadi Salehi
Abstract: We investigate how reform in governmental accounting affects fiscal policy outcomes including debt, balance, and fiscal transparency. Since a change from cash to accrual accounting can be regarded as a natural experiment among governments, a fixed‐effects model is exploited. We discover that the change diminishes debt in developed countries, but expands it in less‐developed ones, with strong effects in highly indebted countries. The change improves balance in developed countries and worsens it in less‐developed countries, which is significant for developed countries with large deficits. Transparency is improved only in less transparent developed countries.